2007
DOI: 10.1038/sj.jhh.1002209
|View full text |Cite
|
Sign up to set email alerts
|

The interarm blood pressure difference as predictor of cardiovascular events in patients with hypertension in primary care: cohort study

Abstract: Objectives of this study were to measure the prevalence of a difference in blood pressure (BP) between arms and determine whether a difference is associated with increased risk of cardiovascular events or death. A prospective cohort study of 247 patients with hypertension was undertaken in one rural general practice in England. The main outcome measures were mean difference in BP between arms and new episodes of myocardial infarction, cerebrovascular event, onset of angina or peripheral vascular disease or dea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
74
3
8

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(93 citation statements)
references
References 25 publications
8
74
3
8
Order By: Relevance
“…But there were no reports about the quantitative correlation between the differences of simultaneously measured IABP and ABI or baPWV. In contrast with our results, some studies 2,15,19) showed that low ABI, ABI less than 0.9, or high baPWV was correlated with inter-arm SBP difference.…”
Section: Discussioncontrasting
confidence: 56%
“…But there were no reports about the quantitative correlation between the differences of simultaneously measured IABP and ABI or baPWV. In contrast with our results, some studies 2,15,19) showed that low ABI, ABI less than 0.9, or high baPWV was correlated with inter-arm SBP difference.…”
Section: Discussioncontrasting
confidence: 56%
“…Other studies have reported a prevalence of inter-arm differences in BP ranging from 12.0 to 18.4% for a systolic difference (sIAD) X20 mmHg and from 13.0 to 33.7% for a diastolic difference (dIAD) X10 mm Hg in various populations (8). In contrast, the systolic and diastolic BP differences were -1.18 mmHg and 0.72 mmHg for SBP and DBP, respectively in this rural Kenyan community population.…”
Section: Discussionmentioning
confidence: 44%
“…It was first recognised more than 100 years ago [8]. Hence, 13 out of 15 blood pressure guidelines recommend that BP should be measured on both arms during initial clinical evaluation [16,17] and the arm with the higher BP be used at subsequent visits, but there is little evidence that this is followed [18].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations